PREDICTABILITY OF MAJOR SWEDISH EXCHANGE RATES - TAH, Kenneth A. (Journal of Advanced Studies in Finance, 2013)
This paper investigates the predictability of weekly percentage changes in exchange rates for Swedish currency-Swedish krona with respect to the currency of major trading partners - namely Danish Krone of Denmark, Norwegian Krone of Norway, US Dollar of United States, UK Pound of United Kingdom and Euro of Germany and Finland. The Exponential GARCH-in-mean (EGARCH) model is used in this study along with a Generalized Error Distribution to allow for variable kurtosis in the data. Percentage changes in the Swedish krona with respect to all partners’ currencies are serially correlated - that is there is a significant first-moment dependency of each exchange rate series. Squared exchange rates for all series also have serial correlation indicating the presence of conditional heteroskedasticity. The series also exhibits opposing movements in order to maintain an orderly market. Conditional mean is not affected by conditional volatility. However, news about volatility from the previous period has explanatory power on current volatility. With respect to Danish Krone and Eurozone Euro, unexpected depreciation or negative shocks of Swedish Krona implies a higher next period conditional variance than its appreciation or positive shocks of the same magnitude. On the other hand, with respect to Norwegian Krone, US Dollar and UK Pound unexpected depreciations or appreciations of Swedish Krona have a symmetric impact on volatility.